Issues and challenges of implementing e-governance in developing countries: a comprehensive analysis of civil service models - Shuaib M. Abdulnabi (Cogent Business & Management, 2024)
The e-government approach continually changes the ways in which the government system serves the public. E-Services include a number of necessary steps to ensure the successful realization of services by institutions for development and administration. This article covers the e-growing services' trends, effectiveness, and the problems associated with addressing the situation, with a view to providing efficient services. The study is organized into key sections, beginning with an introduction that outlines the research problem and objectives. The Background Theory provides insights into existing knowledge on e-governance challenges and civil service models. The theoretical framework establishes the conceptual basis, while the methodology section details the research design and data analysis techniques. In order to generate data for the case study, content analysis and survey methods were employed. The research suggests that the virtual nature of the Internet and its dynamics can enhance public service and new users' ability to conduct secure transactions in e-commerce. The study concluded that e-Government is necessary to manage future problems and respond to current and historical occurrences in order to improve people's confidence. Knowledge regarding the reduction of present and future inefficiencies, the probability of efficiency, and the cost of alternative outcomes helps mitigate their effects. Regulatory, legal, engineering, and procedural procedures, as well as education, capacity building, and continual updating of technology, pose challenges related to e-service. The main problems in public service involve the three levels of staff and management: seamless management and coordination at the federal, provincial, and local levels.
Keywords: 650; Civil service; e-Governance; E-strategy; developing countries